2013
DOI: 10.2190/ns.23.2.e
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Front-Line Hospital Workers' Contributions to Patient and Worker Safety

Abstract: Concerns about stubbornly persistent high rates both of error-related patient injuries and of occupational injuries among healthcare workers have generated intense exploration of etiologies, interventions, and the role of underlying safety culture. Much of this work has centered on the role of physicians and nurses in health care, and suggests common issues related to safety culture. However, the role of front-line health care workers, such as nursing assistants, ward clerks, environmental service workers, foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The sampling frame of 15 488 agencies was developed through three data sources1: the Centers for Medicare and Medicaid Services Providers of Services file of home health agencies and hospice2; state licensing lists of home health agencies of private organisations and3 the National Hospice and Palliative Care Organization file of hospices. The NHHAS was fielded to HHAs at a nationally represented subset of agencies (n=3377) participating in the 2007 NHHCS (n=955).…”
Section: Design and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sampling frame of 15 488 agencies was developed through three data sources1: the Centers for Medicare and Medicaid Services Providers of Services file of home health agencies and hospice2; state licensing lists of home health agencies of private organisations and3 the National Hospice and Palliative Care Organization file of hospices. The NHHAS was fielded to HHAs at a nationally represented subset of agencies (n=3377) participating in the 2007 NHHCS (n=955).…”
Section: Design and Methodsmentioning
confidence: 99%
“…A total of 4836 workers were killed, and millions of others were injured by preventable injuries occurring at the workplace across all industries in 2015 1. This study defined occupational injury as any type of injury reported by a worker at the workplace that occurred during performing job-related responsibilities in a 12-month period 2. At the workplace, workers are at risk for exposure to hazards and occupational accidents that may lead to injury or illness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations